The Influence of Lecturer Roles and Teaching Methods on Student Motivation and Learning Satisfaction - Ramadhani, Astyta Rianti; Nursaldiaman, Muhammad; Syahraka, Muh; Nurfauliah; Sahabuddin, Romansyah; Husain, Fakhirah (Candela Edutech Indonesia, 2025)
The Objectives – This study aims to analyze the influence of lecturers' roles and teaching methods on students' learning motivation and satisfaction. The Methods – The research method used is quantitative with a survey approach through a questionnaire. Data were collected using questionnaires distributed to 250 students at universities in Indonesia. The independent variables include the role of lecturers (as facilitators, motivators, and evaluators) and teaching methods (lectures, discussions, and project-based learning), while the dependent variables are learning motivation and learning satisfaction. Data analysis was conducted using multiple linear regression with the assistance of SPSS 13.0 and Lisrel 8.50. The Results – The results of the study indicate that the role of lecturers and teaching methods have a significant influence on learning motivation (p < 0.05) and learning satisfaction (p < 0.05). Specifically, project-based learning methods contributed the most to learning satisfaction. The Research Implications – The implications of this research emphasize the importance for lecturers to continuously develop pedagogical competencies and to select varied teaching methods in order to enhance students' learning motivation and satisfaction. These findings can serve as a reference for educational institutions in designing more effective lecturer training programs and curricula